Digital Dilemma: The Cognitive Impact of Social Media on Early Childhood in Rural Communities - Utami, Purni (Contemporary Society and Politics Journal, 2025)
The use of social media among early childhood populations has increased significantly, including in rural communities, in line with technological advancements and growing internet accessibility. This study analyzes the impact of social media on early childhood development using a qualitative-descriptive approach through observation and interviews, and is interpreted through Albert Bandura’s social learning theory. The primary focus of this research is to explore how social media influences the cognitive aspects and socialization processes of children in rural settings, particularly in Lekor Village, Janapria District, Central Lombok Regency. The findings reveal a dualistic influence of social media. On the one hand, social media functions as an informal learning tool that enhances children's early cognitive abilities, encourages them to stay indoors, and provides both entertainment and educational content that supports the development of verbal memory. In settings where peer interaction is limited, social media often serves as a substitute for social companionship. On the other hand, social media has emerged as a new agent of socialization that carries significant risks. Young children tend to imitate behaviors portrayed in digital content that may not align with local cultural values. Negative effects identified include poor communication skills, impulsive behavior, disrupted sleep and eating patterns, anxiety, materialistic tendencies, and exposure to inappropriate content. This study underscores the urgent need for community-based digital literacy initiatives and active supervision by parents and local authorities to ensure that social media functions as an educational resource rather than a source of developmental dysfunction in early childhood.